Blended Learning Matakuliah Sepakbola untuk Mahasiswa Pendidikan Jasmani Kesehatan dan Rekreasi - Estrado Isaci Selestiano Rodriquez; Wasis Djoko Dwiyogo; Supriyadi Supriyadi (Graduate School of Universitas Negeri Malang, 2020)
Abstract: The purpose of this research and development is (1) to produce a teaching material product for football courses based on blended learning (face to face, offline, online) and (2) test the effectiveness, efficiency and attractiveness of development products. The results from product specifications research and development for teaching materials football courses based on blended learning following: (1) face-to-face method using printed books, (2) offline methods using interactive multimedia autoplay media studio 8.0, (3) online methods utilizing virtual classes edmodo. The overall results of the average attractiveness test of product development teaching materials using face to face, offline, and online methods satisfy very interesting criteria.Abstrak: Tujuan penelitian dan pengembangan ini adalah (1) menghasilkan sebuah produk bahan ajar matakuliah sepakbola berbasis blended learning (tatap muka, offline, online) dan (2) menguji efektivitas, efisiensi, dan daya tarik produk pengembangan. Spesifikasi produk hasil pengembangan berupa bahan ajar tata muka menggunakan buku cetak, bahan ajar offline menggunakan multimedia interaktif berupa autoplay media studio 8.0, dan untuk bahan ajar online menggunakan kelas virtual yaitu edmodo. Hasil keseluruhan rata-rata uji daya tarik bahan ajar produk pengembangan menggunakan metode tatap muka, offline, dan online adalah sangat menarik.